Colour formation of dihydroxyacetone with cysteine and its derivatives via Maillard reaction. (December 2022) - Sun, Yufa; Al-Zahrani, Fatimah A.M.; Lin, Long
Abstract: Compared to the conventional solar tanning, sunless tanning has become the most popular way to obtain tanned skin due to convenience and safety. Dihydroxyacetone (DHA), a three-carbon sugar, is the main active ingredient in commercial sunless tanning products and its tanning chemistry is similar to the well-known Maillard reaction. Whereas most studies concerning sunless tanning reaction, over the past 60 years, have focused on the amino groups of amino acids, little information is available on the impact of thiol groups of cysteine on the colour formation with DHA. Hence, this study systematically investigated the colour formation of cysteine and DHA using a simplified model system at different molar ratios, reaction times, pH, and temperatures. The colour change and characteristics were quantitatively evaluated using colour difference ( Δ E * ) and CIE L*a*b* values, respectively. In addition, the reactivity of amino and thiol groups on the same cysteine with DHA was further investigated. It was found, for the first time, that the thiol group of cysteine significantly inhibited the colour formation with DHA, while its amino group has a strong colour-formation ability in anhydrous condition. This work not only presents a systematic study on the colour formation of cysteine with DHA and the role of its amino and thiol groups, but also provides new knowledge for understanding and controlling the colour formation of DHA tanning on human skin. Graphical abstract: Image 1 Highlights: Dihydroxyacetone (DHA)–cysteine (Cys) colour formation systematically investigated. Colour change and colour properties of DHA–Cys evaluated using CIELAB colour space. Colour-formation ability of Cys amino/thiol groups-DHA evaluated for the first time. Cysteine thiol groups inhibit colour formation of Cysteine amino groups with DHA.